Trustworthy Tricksters: Violating a Negative Social Expectation Affects Source Memory and Person Perception When Fear of Exploitation Is High - Süssenbach, Philipp; Gollwitzer, Mario; Mieth, Laura; Buchner, Axel; Bell, Raoul (Frontiers in Psychology, 2016)
People who are high in victim-sensitivity—a personality trait characterized by a strong fear of being exploited by others—are more likely to attend to social cues associated with untrustworthiness rather than to cues associated with trustworthiness compared with people who are low in victim-sensitivity. But how do these people react when an initial expectation regarding a target’s trustworthiness turns out to be false? Results from two studies show that victim-sensitive compared with victim-insensitive individuals show enhanced source memory and greater change in person perception for negatively labeled targets that violated rather than confirmed negative expectations (the “trustworthy trickster”). These findings are in line with recent theorizing on schema inconsistency and expectancy violation effects in social cognition and with research on the different facets of justice sensitivity in personality psychology.